KARAKTERISTIK BAMBU ATER BANYUWANGI LAMINASI SUSUNAN LURUS BERDASARKAN KUAT TEKAN DAN KUAT LENTUR - Rifqi, Mirza Ghulam; Amin, M Shofi'ul; Bachtiar, Riza Rahimi; Suryani, Erna; Murdani, Riko (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2022)
Abstract: Laminated bamboo is a building material using a manufacturing technique which is made by bonding several pieces of bamboo. Laminated bamboo has higher characteristic strength compared to natural bamboo and is more mechanical in nature. For lamination treatment arranged straight on the lamination. Pertaining to SNI-03- 3958-1995, SNI-03-3399-1994, SNI 03-3959-1995 and ISO 22157-1; 2019 for the manufacturing and testing procedures for ater banyuwangi bamboo laminate test specimens. The purpose of this study was to work out the characteristics of bamboo ater lamination. The characteristics of bamboo include tensile strength, compressive strength and bending strength. The thickness of bamboo slats of the lamina is 7 mm with a horizontal straight arrangement and uses PVA adhesive. In this study, bamboo originating from the Genteng area in Banyuwangi was used, which was 3- 5 years old. The bamboo soaked in borax for five days for preservation. Bamboo is dried within the sun to dry the air and reduce moisture content (Water content uses 12.5% -15%). Bamboo that has been dried is laminated during a straight arrangement. Testing of bamboo for the lamina using one point load. The results showed that the compressive strength, bending strength and tensile strength of laminated bamboo without preservation were 279,40 kg/cm2, 933,04 kg/cm2 dan 4.700,23 kg/cm2 Mpa respectively, and while the value of compressive strength, bending strength and tensile strength of laminated bamboo with preservation were respectively were 231,62 kg/cm2, 739,94 kg/cm2 dan 4.263,96 kg/cm2. Based on the results of compress strength values, bending strength and tensile strength, the characteristics of bamboo ater banyuwangi laminate are classified with a strong class approach of wood and wood quality code including in strong class II according to PKKI NI-5 1961 and quality code E25 according to SNI 7973 2013..Keywords : laminated bamboo, water content, bending strength, compressive strength, tensile strength.Abstrak: Bambu laminasi merupakan bahan bangunan dengan teknik pembuatan yang dibuat dengan mengikat beberapa batang bambu. Bambu laminasi memiliki karakteristik kekuatan yang lebih tinggi dibandingkan dengan bambu alami dan lebih bersifat mekanis. Untuk perawatan laminasi diatur langsung pada laminasi. Terkait dengan SNI-03- 3958-1995, SNI-03-3399-1994, SNI 03-3959-1995 dan ISO 22157-1; 2019 untuk prosedur pembuatan dan pengujian benda uji laminasi bambu ater banyuwangi Tujuan penelitian ini adalah untuk mengetahui karakteristik laminasi ater bambu. Karakteristik bambu meliputi kuat tarik, kuat tekan dan kuat lentur. Ketebalan bilah bamboo untuk lamina 7 mm dengan susunan lurus horizontal dan menggunakan perekat PVA. Penelitian ini menggunakan bambu yang berasal dari daerah Genteng di Banyuwangi yang berumur 3 - 5 tahun. Bambu direndam dalam boraks selama lima hari untuk pengawetan. Bambu dikeringkan di bawah sinar matahari untuk mengeringkan udara dan mengurangi kadar air (Kadar air menggunakan 12,5% -15%). Bambu yang sudah dikeringkan dilaminasi dengan penataan lurus. Metode pengujian untuk lamina menggunakan pembebanan satu titik. Hasil penelitian menunjukkan bahwa kuat tekan, kuat lentur dan kuat tarik bambu laminasi tanpa pengawetan masing-masing adalah 279,40 kg/cm2, 933,04 kg/cm2 dan 4.700,23 kg/cm2, sedangkan nilai kuat tekan, kuat lentur dan kuat tarik bambu laminasi dengan pengawetan masing-masing sebesar 231,62 kg/cm2, 739,94 kg/cm2 dan 4.263,96 kg/cm2. Berdasarkan hasil nilai kuat tekan, kuat lentur dan kuat tarik maka karakteristik bambu ater banyuwangi laminasi diklasifikasikan dengan pendekatan kelas kuat kayu serta kode mutu kayu termasuk pada kelas kuat II menurut PKKI NI-5 1961 dan kode mutu E25 menurut SNI 7973 2013.Kata kunci : bambu laminasi, kadar air, kuat lentur, kuat tekan, kuat tarik